Ibnu Taimiyah’s Thoughts Relevance to the Constitutional Court Decision No. 46/2012 on the Illegitimate Children Lineage - Amri Amir; Rahmi Wiza; Ibrahim bin Salem Al-Saedy (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
The societal perception of illegitimate children often carries negative connotations, despite their entitlement to clear legal rights. One of the classical scholars, Ibn Taimiyah, offers distinct perspectives on the lineage and rights of children born outside of marriage, aligning with the principles laid out in Constitutional Court Decision No. 46/2012. This study aims to analyze Ibn Taimiyah's viewpoints regarding the lineage and civil rights of illegitimate children, while also examining their relevance to the aforementioned court decision. Employing a descriptive analysis method with a literature review approach, this research draws primarily from Ibn Taimiyah's seminal work,